Determinan Perilaku Pencegahan COVID-19 - Wardani, Rosita Kusuma (Universitas Veteran Bangun Nusantara, 2023)
Background: The impact that occurred during the COVID-19 pandemic was a change in people's behavior who tried to implement the COVID-19 prevention protocol, namely wearing masks, washing hands and keeping their distance. So that the existing prevention behavior must be the key to implementation in health services and the community. Research objective: to find out the factors related to COVID-19 prevention behavior. Methods: This study used a cross-sectional design with a total sample of 100 respondents. The instrument used is a questionnaire. The independent variables studied were age, gender, education level, type of work, knowledge, perceptions, attitudes. The dependent variable studied was the behavior of preventing COVID-19. Data analysis was carried out univariately and bivariately, using the chi squarogistic regression (? = 0.05). Results: There is a relationship between prevention behavior for the transmission of COVID-19 age (0.016), gender (0.019), level of education (0.023, knowledge (0.036), perception (0.015), attitude (0.04). There is no relationship between prevention behavior transmission of COVID-19 by type of work (0.83). Conclusion: There is a significant relationship between age, gender, education level, knowledge, perceptions, attitudes, and behavior to prevent transmission of COVID-19.